Simulation of shock-induced melting of Ni using molecular dynamics coupled to a two-temperature model - Koci, L; Bringa, E; Ivanov, D; Hawreliak, J; McNaney, J; Higginbotham, A; Zhigilei, L; Belonoshko, AB; Remington, B; Ahuja, R (2006)
Using nonequilibrium molecular dynamics (MD) simulations we study shock-induced melting in Ni with an embedded atom method (EAM). Dynamic melting is probed by the pair correlation function, and we find a melting lattice temperature of Tmelt =6400±300 K for a melting pressure of Pmelt =275±10 GPa. When a combined MD+TTM (two-temperature model) approach is used to include electronic heat conduction and electron-phonon coupling, Pmelt and Tmelt change. For a given pressure, the temperature behind the shock decreases due to electronic heat diffusion into the cold, unshocked material. This cooling of the material behind the shock slightly increases the melting pressure compared to simulations without electronic heat conduction and electron-phonon coupling. The decrease in the temperature behind the shock front is enhanced if the electron-phonon coupling is artificially made larger. We also explore the feasibility of using x-ray diffraction to detect melting. © 2006 The American Physical Society.